Does the relative population growth affect purchasing power parity? - Salim, Ruhul; Hassan, K. (Routledge, Taylor and Francis Ltd, 2009)
Relative population growth affects price levels through its effect on money demand and that in turn impacts Purchasing Power Parity (PPP). Standard time series econometrics is used to investigate this issue using data from 30 selected countries. The empirical results show that there is stable relationship between PPP exchange rate and relative population growth in selected countries in the long run. These findings demonstrate that population growth influences exchange rate determination through PPP.